"Look, a [picture]!": Visuality, race, and what we do not see. Issue 1 (2nd January 2016) - Kaszynski, Elizabeth
ABSTRACT: This article argues that understanding vision and visuality as associated but distinct terms has significant implications for the ways in which we engage with racial constructions of identity. Expanding the ways in which we visualize race beyond simply the visual offers us a more comprehensive approach to understanding the construction of and response to race in the twenty-first-century United States. This article moves from theoretical implications of non-visual visualizations like tactile visuality and audial visuality through photographs taken by blind photographers to ask how race and racial identity are implicated in conversations about both vision and visuality.